Sand mining in Africa: Value chains, sustainability dilemmas, and key lessons for extractive industries - Bernard Lutalo; Baker Matovu; Isaac Sarfo; Henry Musoke Semakula; Paul Mukwaya; Nelson Turyahabwe; Alex Ronald Mwangu (The Extractive Industries and Society, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Evolution of Southern Ocean Net Primary Production in a Changing Climate: Challenges and Opportunities - Alessandro Tagliabue; Thomas Ryan‐Keogh; Alex Baker; Thomas S. Bibby; Chris Follett; Maeve C. Lohan; Alberto Naveira‐Garabato; Daniel J. Mayor; Angela Milne; C. Mark Moore; Simon Ussher (Global Change Biology, 2025)
Net primary production in the Southern Ocean plays a critical role in governing ecosystem production, the biological carbon pump, and global biogeochemical cycles. Recent work has advanced our understanding of novel factors regulating Southern Ocean net primary production and the regional physiological adaptations employed by Southern Ocean phytoplankton in terms of their photosynthetic strategies and resource acquisition. Here we assess trends in Southern Ocean net primary production from different remote sensing algorithms and bgc‐Argo floats to compare them to the latest Earth System Models used to forecast future changes under three different future climate scenarios. Overall, remote sensing and bgc‐Argo floats indicate net primary productivity in the Southern Ocean is declining at basin scale. This contrasts with the Earth System Models that display muted contemporary trends and consistent increases in net primary production that are relatively robust across SSP2‐45, SSP3‐70, and SS5‐85. This mismatch in trends suggests low confidence in these projected net primary production changes, with implications for assessments of changes in ecosystem services. Despite their coherence in terms of net primary production trends, Earth System Models show large disagreement in the relative role of different drivers, suggesting we lack sufficient mechanistic understanding. Improved knowledge of the role of manganese alongside iron and the coupled responses of phytoplankton and zooplankton through the integration of observations and experiments into a new generation of models is necessary to deliver confident forecasts of Southern Ocean ecosystem change. Advancing knowledge in these areas is an important priority for future research in the region and provides context for policy discussions around the marine protection of Antarctic ecosystems that depend on sufficiently confident projections of climate change impacts.

Sublethal juvenile dioxin (TCDD) exposure alters sperm motility and whole-body vitellogenin parameters in adult male zebrafish (Danio rerio) - Danielle N Meyer; Gabrielle F. Gonzalez; Jonathan R Cowart; Alex Haimbaugh; Nicole M Dennis; Tracie R Baker (Aquatic Toxicology, 2025)

Whole Genome Sequencing Reveals How Plasticity and Genetic Differentiation Underlie Sympatric Morphs of Arctic Charr - Khrystyna Kurta; Mariano Olivera Fedi; Kendall Baker; Tom Barker; Leah Catchpole; Claudio Ciofi; Arianna Cocco; Joanna Collins; Genevieve Diedericks; Maria Angela Diroma; Alex Durrant; Kjetil Hindar; et al. (Molecular Ecology, 2025)
Salmonids have a remarkable ability to form sympatric morphs after postglacial colonisation of freshwater lakes. These morphs often differ in morphology, feeding and spawning behaviour. Here, we explored the genetic basis of morph differentiation in Arctic charr ( n = 283) by first establishing a high‐quality reference genome and then using this in whole genome sequencing of distinct morphs present in two Norwegian and two Icelandic lakes. The four lakes represent the spectrum of genetic differentiation between morphs from one lake with no genetic differentiation between morphs, implying phenotypic plasticity, to two lakes with locus‐specific genetic differentiation, implying incomplete reproductive isolation, and one lake with strong genome‐wide divergence consistent with complete reproductive isolation. As many as 12 putative inversions ranging from 0.45 to 3.25 Mbp in size segregated among the four morphs present in one lake, Thingvallavatn, and these contributed significantly to the genetic differentiation among morphs. None of the putative inversions were found in any of the other lakes, but there were cases of partial haplotype sharing in similar morph contrasts in other lakes. Our findings are consistent with a highly polygenic basis of morph differentiation with population‐specific selection on alleles linked to the development of similar morph phenotypes. The results support a model where morph differentiation is first established through phenotypic plasticity, leading to niche expansion and separation. This may be followed by gradual development of reproductive isolation, locus‐specific differentiation and eventually complete reproductive isolation and genome‐wide divergence.

Evaluating the effective segmentation of human lateral geniculate nucleus - Lauren E. Welbourne; Joel T. Martin; Federico G. Segala; Anisa Y. Morsi; Daniel H. Baker; Alex R. Wade (Brain Structure and Function, 2025)
Important parts of the visual pathway occur in relatively small subcortical structures that are often difficult to identify and segment using standard structural scans in MRI (e.g. T1 and T2 scans). Studies of the Lateral Geniculate Nucleus (LGN) often use proton density (PD) scan protocols, repeated up to 40 times, then manually segment the LGN structure from the average image. Efficiency is crucial when conducting MRI scans: minimising time spent on structural scanning can increase time available for complementary functional MRI scans and/or reduce scanning costs. In this study we asked how segmentation accuracy depended on the number of PD repeats. Four raters segmented the LGN of five participants, using different numbers of PD scans in the average image (1, 2, 4, 8, 16, 24, 32, 40), and an additional experienced expert rater segmented the LGN for just the 40PD average for all participants. We compared how the rater LGN masks at each scan average level overlapped with the expert masks. One rater performed the segmentation for the 40PD average on four separate days, to measure intra-rater variability across repeats. We also used a state-of-the-art automated segmentation process to compare the reliability to manual segmentation. We found that the average overlap between rater masks and the expert masks increased up to the 16PD scan average level, after which there was no additional benefit to including more PD scans. The automated segmentation masks were comparable to the overlap between the raters (40PD) and expert masks.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

How much data do you need? An analysis of pelvic multi-organ segmentation in a limited data context - Febrio Lunardo; Laura Baker; Alex Tan; John Baines; Timothy Squire; Jason A. Dowling; Mostafa Rahimi Azghadi; Ashley G. Gillman (Physical and Engineering Sciences in Medicine, 2025)
Training deep learning models generally requires large, costly datasets which can limit their application towards in-house segmentation tasks. This study investigates the trade-off in dataset size within the context of pelvic multi-organ MR segmentation where we evaluate the performance of nnU-Net, a well-known segmentation model, under conditions of limited domain and data availability. 12 participants undergoing treatment on an Elekta Unity were recruited, acquiring 58 MR images, with 4 participants (12 images) withheld for testing. Prostate, seminal vesicles (SV), bladder and rectum were contoured in each image by a radiation oncologist. Seven models were trained on progressively smaller subsets of the training dataset, simulating a limited dataset setting. To investigate the efficacy of data augmentation, another set of identical models were trained without augmentation. The performance of the networks was evaluated via the Dice Similarity Coefficient, mean surface distance, and 95% Hausdorff distance metrics. When trained with entire training dataset (46 images), the model achieved a mean Dice coefficient of 0.903 (Prostate), 0.851 (SV), 0.884 (Rectum) and 0.967 (Bladder). Segmentation performance remained stable when the number of training sets was > 12 images from 4 participants, but rapidly dropped in smaller data subsets. Data augmentation was found to be influential across all dataset sizes, but especially in very small datasets. This study demonstrated nnU-Net's proficiency in performing male pelvic multi-organ segmentation under a limited domain, a single scanner, and under limited data constraints. We found that the performance degradation was often modest until a threshold is reached (12 images), below which it dropped significantly. Data augmentation improved performance across all data sizes, but especially for very small datasets. We conclude that nnU-Net’s low data requirement can be advantageous for in-house cases with consistent protocol and scarce data availability.

Thoracic Responses and Injuries of Male Post-Mortem Human Subjects in a Homogeneous Rear-Facing Seat During High-Speed Frontal Impact - Yun-Seok Kang; Gretchen H. Baker; Timothy DeWitt; Angelo Marcallini; Vikram Pradhan; Angela Tesny; Alex Bendig; Zachary Haverfield; Amanda M. Agnew; John H. Bolte (Annals of Biomedical Engineering, 2025)

Calculating carbon: The value of information in precision for blue carbon restoration projects - Alice J. Twomey; Alex Baker; Nathan Waltham; Catherine E. Lovelock (Journal of Environmental Management, 2024)

Correction: A case of suspected chimpanzee scavenging in the Issa Valley, Tanzania - Sam A. Baker; Fiona A. Stewart; Alex K. Piel (Primates, 2024)

A case of suspected chimpanzee scavenging in the Issa Valley, Tanzania - Sam A. Baker; Fiona A. Stewart; Alex K. Piel (Primates, 2024)

Response of coccolithophore communities to oceanographic and atmospheric processes across the North- and Equatorial Atlantic - Catarina V. Guerreiro; Afonso Ferreira; Lluisa Cros; Jan-Berend Stuut; Alex Baker; Andreia Tracana; Catarina Pinto; Vera Veloso; Andrew P. Rees; Mário A. P. Cachão; Telmo Nunes; Vanda Brotas (Frontiers in Marine Science, 2023)
Changes in coccolithophore productivity in response to climate-driven ocean warming are likely to have cascading biogeochemical effects that feed back to the changing climate. This paper investigates the role (and interplay) of large-scale oceanographic and atmospheric processes across the North- and Equatorial Atlantic, including Saharan dust deposition, on the distribution of coccolithophore communities. The study is based on biological and hydrological data collected across the photic zone of the ocean, and aerosol data collected from the lower atmosphere, across 50°N–1°S during the Atlantic Meridional Transect in boreal Autumn of 2018 (AMT28), in synergy with Earth Observations. Results confirm existing understanding of the distribution of coccolithophore communities which are related to major meridional hydrological gradients across the North Atlantic. Dynamic, oxygenated and microphytoplankton-enriched waters at higher-latitudes were characterized by less diverse coccolithophore populations, dominated by placolith-bearing r-selected coccolithophores. In contrast, the heavily stratified and picoplankton-enriched waters of the subtropical gyre revealed more diverse populations, dominated by umbelliform coccolithophores and holococcolithophores at the surface, and by floriform taxa in the lower photic zone. Mean concentrations of 14.4×10 3 cells/L present in the North Atlantic Tropical Gyre Province (30–12°N), only slightly lower compared to 17.7×10 3 cells/L produced in the North Atlantic Drift province (50–40°N), provide a snapshot perspective on the importance of coccolithophore production in heavily stratified gyre conditions. Higher concentrations of 19’-Hexanoyloxyfucoxanthin (HexFuco) in regions of enhanced production of r-selected placolith-bearing species suggest that this pigment should not be generalized as a proxy for the entire coccolithophore community. Enhanced abundances of fast-blooming Emiliania huxleyi and Gephyrocapsa oceanica , and of cyanobacteria (including both picoplankton and N 2 -fixing Trichodesmium spp.) at the surface of the region of more persistent Saharan dust deposition (at ~12-10°N) appeared to result from dust-born nutrient input. Underneath this stratified surface layer, enhanced productivity in the deep chlorophyll maximum (DCM) appeared decoupled from that on the surface, fueled by geostrophic eastward shoaling of the nutricline across the tropical North Atlantic. As this was the region of highest macronutrient concentrations measured along and below the nutricline, our data suggest that the NE tropical Atlantic may act as a permanent dust-born nutrient depocenter as previously hypothesized.

Transforming environmental performance through inventory, assessment, and validation: a case study of the Los Alamos National Laboratory Waste Compliance and Tracking System - Oral S. Saulters; Shanon D. Goldberg; Wendy A. Staples; Ellena I. Martinez; Lorie M. Sanchez; Diego E. Archuleta; Deborah L. Williams; Scot D. Johnson; Alex M. Baker; Bethann McVicker (Journal of Environmental Studies and Sciences, 2023)

Soluble Iodine Speciation in Marine Aerosols Across the Indian and Pacific Ocean Basins - Elise S. Droste; Alex R. Baker; Chan Yodle; Andrew Smith; Laurens Ganzeveld (Frontiers in Marine Science, 2021)
Iodine affects the radiative budget and the oxidative capacity of the atmosphere and is consequently involved in important climate feedbacks. A fraction of the iodine emitted by oceans ends up in aerosols, where complex halogen chemistry regulates the recycling of iodine to the gas-phase where it effectively destroys ozone. The iodine speciation and major ion composition of aerosol samples collected during four cruises in the East and West Pacific and Indian Oceans was studied to understand the influences on iodine’s gas-aerosol phase recycling. A significant inverse relationship exists between iodide (I – ) and iodate (IO 3 – ) proportions in both fine and coarse mode aerosols, with a relatively constant soluble organic iodine (SOI) fraction of 19.8% (median) for fine and coarse mode samples of all cruises combined. Consistent with previous work on the Atlantic Ocean, this work further provides observational support that IO 3 – reduction is attributed to aerosol acidity, which is associated to smaller aerosol particles and air masses that have been influenced by anthropogenic emissions. Significant correlations are found between SOI and I – , which supports hypotheses that SOI may be a source for I – . This data contributes to a growing observational dataset on aerosol iodine speciation and provides evidence for relatively constant proportions of iodine species in unpolluted marine aerosols. Future development in our understanding of iodine speciation depends on aerosol pH measurements and unravelling the complex composition of SOI in aerosols.

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Tumor shedding and metastatic progression after tumor excision in patient-derived orthotopic xenograft models of triple-negative breast cancer - Aryana M. Razmara; Elodie Sollier; Grace N. Kisirkoi; Sam W. Baker; Margot B. Bellon; Alex McMillan; Clementine A. Lemaire; Vishnu C. Ramani; Stefanie S. Jeffrey; Kerriann M. Casey (Clinical & Experimental Metastasis, 2020)

Correction to: Development and Multi-Scale Validation of a Finite Element Football Helmet Model - William B. Decker; Alex M. Baker; Xin Ye; Philip J. Brown; Joel D. Stitzel; F. Scott Gayzik (Annals of Biomedical Engineering, 2020)

Mechanistic Deconvolution of Oral Absorption Model with Dynamic Gastrointestinal Fluid to Predict Regional Rate and Extent of GI Drug Dissolution - Alex Yu; Mark J. Koenigsknecht; Bart Hens; Jason R. Baker; Bo Wen; Trachette L. Jackson; Manjunath P. Pai; William Hasler; Gordon L. Amidon; Duxin Sun (The AAPS Journal, 2020)

Development and Multi-Scale Validation of a Finite Element Football Helmet Model - William Decker; Alex Baker; Xin Ye; Philip Brown; Joel Stitzel; F. Scott Gayzik (Annals of Biomedical Engineering, 2020)
Head injury is a growing concern within contact sports, including American football. Computational tools such as finite element (FE) models provide an avenue for researchers to study, and potentially optimize safety tools, such as helmets. The goal of this study was to develop an accurate representative helmet model that could be used in further study of head injury to mitigate the toll of concussions in contact sports. An FE model of a Schutt Air XP Pro football helmet was developed through three major steps: geometry development, material characterization, and model validation. The fully assembled helmet model was fit onto a Hybrid III dummy head–neck model and National Operating Committee on Standards for Athletic Equipment (NOCSAE) head model and validated through a series of 67 representative impacts similar to those experienced by a football player. The kinematic and kinetic response of the model was compared to the response of the physical experiments, which included force, head linear acceleration, head angular velocity, and carriage acceleration. The outputs between the model and the physical tests were quantitatively evaluated using CORelation and Analysis (CORA), amounting to an overall averaged score of 0.76. The model described in this study has been extensively validated and can function as a building block for innovation in player safety.

Ship-Based Contributions to Global Ocean, Weather, and Climate Observing Systems - Shawn R. Smith; Gaël Alory; Axel Andersson; William Asher; Alex Baker; David I. Berry; Kyla Drushka; Darin Figurskey; Eric Freeman; Paul Holthus; Tim Jickells; Henry Kleta; et al. (Frontiers in Marine Science, 2019)

Mechanistic Fluid Transport Model to Estimate Gastrointestinal Fluid Volume and Its Dynamic Change Over Time - Alex Yu; Trachette Jackson; Yasuhiro Tsume; Mark Koenigsknecht; Jeffrey Wysocki; Luca Marciani; Gordon L. Amidon; Ann Frances; Jason R. Baker; William Hasler; Bo Wen; Amit Pai; et al. (The AAPS Journal, 2017)

Heart rate analysis by sparse representation for acute pain detection - Shai Tejman-Yarden; Ofer Levi; Alex Beizerov; Yisrael Parmet; Tu Nguyen; Michael Saunders; Zvia Rudich; James C. Perry; Dewleen G. Baker; Tobias Moeller-Bertram (Medical & Biological Engineering & Computing, 2016)

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Development and Implementation of a Bayesian-based Aquifer Vulnerability Assessment in Florida - Jonathan D. Arthur; H. Alex R. Wood; Alan E. Baker; James R. Cichon; Gary L. Raines (Natural Resources Research, 2007)

Nitrogen Leaching and Denitrification in Continuous Corn as Related to Residue Management and Nitrogen Fertilization - Hero T. Gollany; Jean-Alex E. Molina; C. Edward Clapp; Raymond R. Allmaras; Milegua F. Layese; John M. Baker; H. H. Cheng (Environmental Management, 2004)

Variation in potential for isoprene emissions among Neotropical forest sites - Peter Harley; Pérola Vasconcellos; Lee Vierling; Carlos Cleomir de S. Pinheiro; James Greenberg; Alex Guenther; Lee Klinger; Samuel Soares de Almeida; David Neill; Tim Baker; Oliver Phillips; Yadvinder Malhi (Global Change Biology, 2004)
As part of the Large Scale Biosphere–Atmosphere Experiment in Amazônia (LBA), we have developed a bottom‐up approach for estimating canopy‐scale fluxes of isoprene. Estimating isoprene fluxes for a given forest ecosystem requires knowledge of foliar biomass, segregated by species, and the isoprene emission characteristics of the individual tree species comprising the forest. In this study, approximately 38% of 125 tree species examined at six sites in the Brazilian Amazon emitted isoprene. Given logistical difficulties and extremely high species diversity, it was possible to screen only a small percentage of tree species, and we propose a protocol for estimating the emission capacity of unmeasured taxa using a taxonomic approach, in which we assign to an unmeasured genus a value based on the percentage of genera within its plant family which have been shown to emit isoprene. Combining this information with data obtained from 14 tree censuses at four Neotropical forest sites, we have estimated the percentage of isoprene‐emitting biomass at each site. The relative contribution of each genus of tree is estimated as the basal area of all trees of that genus divided by the total basal area of the plot. Using this technique, the percentage of isoprene‐emitting biomass varied from 20% to 42% (mean=31%; SD=8%). Responses of isoprene emission to varying light and temperature, measured on a sun‐adapted leaf of mango ( Mangifera indica L.), suggest that existing algorithms developed for temperate species are adequate for tropical species as well. Incorporating these algorithms, estimates of isoprene‐emitting biomass, isoprene emission capacity, and site foliar biomass into a canopy flux model, canopy‐scale fluxes of isoprene were predicted and compared with the above‐canopy fluxes measured at two sites. Our bottom‐up approach overestimates fluxes by about 50%, but variations in measured fluxes between the two sites are largely explained by observed variation in the amount of isoprene‐emitting biomass.

MICROGRAVITY CULTURE REDUCES APOPTOSIS AND INCREASES THE DIFFERENTIATION OF A HUMAN COLORECTAL CARCINOMA CELL LINE - J. MILBURN JESSUP; MARYLIN FRANTZ; ENIGUL SONMEZ-ALPAN; JOSEPH LOCKER; KIMBERLY SKENA; HEATHER WALLER; PAUL BATTLE; ALEX NACHMAN; MARY ELLEN WEBER; DONALD A. THOMAS; ROBERT L. CURBEAM, Jr.; TACEY L. BAKER; et al. (In Vitro Cellular & Developmental Biology - Animal, 2000)